Perfeksionisme, Prokrastinasi Akademik, dan Penyelesaian Skripsi Mahasiswa - Gunawinata, Vensi Anita Ria; Nanik; Lasmono, Hari K. (ANIMA Indonesian Psychological Journal, 2008)
The aim of this research was to find out the correlation between perfectionism and aca- demic procrastination in completing a term paper. Respondents were students (N = 232) who are working on their theses or term papers and the 2007-2008 graduates. Data were collected through (a) the Tuckman Procrastination Scale to measure academic procrastination, (b) Perfectionism Inventory to measure perfectionism, and (c) Procrastination Assessment Scale Student part II to explore the procrastination behavior. Results reveal a significant correlation between perfectionism and academic procrastination (r = 0.277). Among the three dimensions of perfectionism, the socially prescribed perfectionism and other-oriented perfectionism have a positive correlation to academic procrasti- nation. Tujuan penelitian ini adalah mengungkap hubungan antara perfeksionisme dan prokrastinasi akademik dalam penyelesaian skripsi mahasiswa. Responden penelitian ini adalah mahasiswa (N = 232) yang sedang menyelesaikan skripsi dan lulusan semester gasal 2007-2008. data diperoleh dengan menggunakan (a) Tuckman Procrastination Scale untuk mengukur prokrastinasi akademik, (b) Perfectionism Inventory untuk mengukur perfeksionisme, dan (c) Procrastination Assessment Scale Student untuk mengetahui alasan seseorang berprokrastinasi. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara perfeksionisme dan prokrastinasi akademik (r = 0.277). Di antara ketiga aspek perfeksionisme, socially prescribed perfectionism dan other-oriented perfectionism memiliki hubungan yang positif terhadap prokrastinasi akademik.